1998
DOI: 10.1136/thx.53.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Familial primary spontaneous pneumothorax consistent with true autosomal dominant inheritance.

Abstract: history of chest problems although he smoked A family exhibiting spontaneous pneumo-20 cigarettes per day. Radiography of the chest thorax in a father and three offspring (two confirmed pneumothorax. He was treated with sons and one daughter) is described. The a chest drain and complete resolution occurred mode of inheritance is apparently auto-with no further episodes. His brother III.5 who somal dominant with two episodes of male was a non-smoker with no previous respiratory to male transmission in one famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 16 publications
4
24
0
Order By: Relevance
“…A history of smoking, height, male sex, and family history are known risk factors for sporadic SP (14). Most cases of SP are sporadic but familial cases have been reported (15)(16)(17)(18). Familial SP is genetically heterogeneous and various patterns of inheritance have been reported, including autosomal dominant (16,18), X-linked recessive (15) and autosomal recessive patterns (17).…”
Section: Birt-hogg-dubé Syndrome (Bhds; Omim [Online Mendelianmentioning
confidence: 99%
“…A history of smoking, height, male sex, and family history are known risk factors for sporadic SP (14). Most cases of SP are sporadic but familial cases have been reported (15)(16)(17)(18). Familial SP is genetically heterogeneous and various patterns of inheritance have been reported, including autosomal dominant (16,18), X-linked recessive (15) and autosomal recessive patterns (17).…”
Section: Birt-hogg-dubé Syndrome (Bhds; Omim [Online Mendelianmentioning
confidence: 99%
“…[6][7][8][9][10][11]13 This can be explained as follows: It was reported by the individuals in this family while their family tree (genealogical research) was being formed that the women in this family circle had suffered from a number of miscarriages. However, no precise information could be received about genders of the infants that were lost through the spontaneous abortions.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the male gender is dominantly affected by FPSP, it can still be seen in both genders. 6,7,10,11 The aim of this study was to investigate the demographic, clinical, laboratory, radiological and hereditary characteristics of 8 PSP cases within an extended family in which frequent consanguineous marriages are seen.…”
mentioning
confidence: 99%
“…5) However, the mechanism of bulla formation remains unclear. It is reported that the development of blebs and bullae appear to be linked to a variety of factors, including distal airway inflammation, 14) hereditary predisposition, 15) ectomorphic physiognomy with more negative intrapleural pressures 16) and apical ischemia, 17) and abnormal connective tissue. 18,19) However, there are many patients with PSP without these risk factors.…”
Section: Discussionmentioning
confidence: 99%